2011
DOI: 10.3109/00365521.2011.627446
|View full text |Cite
|
Sign up to set email alerts
|

National centralization of biliary atresia care to an assigned multidisciplinary team provides high-quality outcomes

Abstract: In small countries, BA treatment should be centralized to appointed multidisciplinary teams allowing high quality results with a median of four cases/year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 32 publications
4
71
1
Order By: Relevance
“…Centralization of these high-complex and low-volume procedures could potentially lead to further improvement of surgical technique and perioperative care and might have a beneficial effect on postoperative outcomes and survival as shown for other high complex (pediatric) surgical procedures [34][35][36]. Further research is necessary, since the effects of caseload and organization of care on outcomes for patients with hepatoblastoma have not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Centralization of these high-complex and low-volume procedures could potentially lead to further improvement of surgical technique and perioperative care and might have a beneficial effect on postoperative outcomes and survival as shown for other high complex (pediatric) surgical procedures [34][35][36]. Further research is necessary, since the effects of caseload and organization of care on outcomes for patients with hepatoblastoma have not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of BA and pediatric liver transplantations are nationally centralized to our unit [7]. A total of 29 BA patients born between 2000 and 2013 were enrolled.…”
Section: Patients and Study Designmentioning
confidence: 99%
“…Surgical treatment consists of the Kasai hepatoportoenterostomy (KPE) (5). Adequate drainage of bile is achieved in 38% to 75% of cases (2,3,6,7). Studies with almost exclusively term BA patients showed that early KPE is associated with better transplant-free survival; a KPE after 60 days of age has a negative effect on transplant-free survival (2,(8)(9)(10).…”
mentioning
confidence: 99%